How price moderates assessments of coffee quality across profiles of gender and experience - D. Priilaid; B. Horwitz (South African Journal of Business Management, 2016)
Proceeding from studies that identify the extrinsic price cue as a mediator between a product's perceived and intrinsic merit, we report on a blind-versus-sighted coffee tasting experiment conducted to determine the impact of the price-cue across coffee-user categories of gender and relative experience. Seven instant coffees were tasted by 100 subjects producing 700 paired blind and sighted tastings. Aggregating the data, OLS regression models were run to estimate price-effects across discrete and overlapping bands of gender and self-confessed expertise (non-expert and expert). Our analysis reveals the extent to which price-effects demean a coffee's intrinsic merit during sighted tastings, with experienced male coffee drinkers most especially susceptible to price persuasion, and less experienced female drinkers the least. Thus our paper introduces a cheap and affective means of testing for such cue-effects. Neuromarketing styles of testing are usually cumbersome, expensive and difficult to scale. The method show-cased here offers a meaningful alternative. These findings uphold the view that the price cue remains a critical tool in the marketing of coffee; most notably because of its potential cost-free contribution to the ramping of experienced pleasure without any augmentation of quality. Further implications are explored.
Keywords: 650